Avaliação do absenteísmo por motivo de doença em funcionários técnico administrativos de uma universidade federal (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Assessment of absenteeism due to illness among technical administrative employees of a federal university